Fertilizer Recommendations based on Target Yield Concept for Cabbage Grown in a Mollisol of Uttarakhand - Sobaran Singh, Jyoti Pande and (Journal of the Indian Society of Soil Science, 2016)
The response of cabbage to the selected combinations of four levels of N (0, 90, 120 and 150 kg ha-1), P2O5 (0, 30, 60 and 90 kg ha-1), K2O (0, 30, 60 and 90 kg ha-1) and three levels of FYM (0, 10 and 20 t ha-1) with simultaneous variations in initially available soil form of these nutrients was studied under AICRP on Soil Test Crop Response (STCR) in an Aquic Hapludoll at Norman E. Borlogue Crop Research Centre of the G.B. Pant University of Agriculture and Technology, Pantnagar during 2008-09 and 2009-10. Nutrient requirement to produce one quintal of cabbage head was 0.92, 0.10 and 1.03 kg of N, P2O5 and K2O, respectively. Per cent contribution of N, P and K was 59, 66 and 123 from soil and 59, 14 and 53 from FYM, 85, 9 and 126 from fertilizer, and 104, 11 and 162 from conjoint use of fertilizer and FYM. Using these basic data, fertilizer adjustment equations were developed for prescribing optimum fertilizer doses for different yield targets of cabbage under both chemical as well as integrated nutrient management (INM) mode. The validity of these equations have been tested in the verification trial which showed that fertilizer application based on target yield (250 q ha-1) recorded higher yields, net benefit and B:C ratio over general recommended dose.